IMPLEMENTASI KURIKULUM PAI DI TENGAH PANDEMI COVID-19 DI SMP NEGERI 2 PLERET BANTUL YOGYAKARTA - Imroatum Muhimmah (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2021)
This study aims to describe the implementation of the Islamic Education curriculum, teacher strategies in carrying out learning, and the impact of learning in the midst of the Covid-19 pandemic. This type of research is descriptive with a qualitative approach. The research subjects were the principal, two Islamic Religious Education teachers and ten students. Data collection techniques using interviews, observation, and documentation and data analysis using data reduction. The results of this study indicate that the implementation of the PAI curriculum at SMP Negeri 2 Pleret in the midst of the Covid-19 pandemic can be categorized as quite good. In the Covid-19 pandemic the PAI curriculum has not changed, but the learning model and assessment of students are adjusted to the pandemic conditions. PAI learning strategies using online or distance, giving assignments to students using WhatsApp groups. PAI learning like this has positive impacts: 1) Teachers and students are technology literate. 2) Teachers are more creative and innovative in providing learning models and strategies. 3) Increase the talents of students. 4) Adding insight to online literature. 5) Increase knowledge about television learning programs. Negative impact: 1) Students who do not understand online learning. 2) The teacher has not received any socialization or workshop on online or distance learning. 3) Lack of parental monitoring. 4) Students procrastinate doing assignments. 5) Inaccurate assessment.